2018
DOI: 10.1002/jbt.22233
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose bisphenol A induces RIPK1‐mediated necroptosis in SH‐SY5Y cells: Effects on TNF‐α and acetylcholinesterase

Abstract: Bisphenol A (BPA) is an endocrine disruptor chemical, which is commonly used in everyday products. Adverse effects of its exposure are reported even at picomolar doses. Effects of picomolar and nanomolar concentrations of BPA on cytotoxicity, nitric oxide (NO) levels, acetylcholinesterase (AChE) gene expression and activity, and tumor necrosis factor‐α (TNF‐α) and caspase‐8 levels were determined in SH‐SY5Y cells. The current study reveals that low‐dose BPA treatment induced cytotoxicity, NO, and caspase‐8 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Our results distincly show that different doses (0-100 μM) of BPA administered for different period may change viability and NO levels of SH-SY5Y neuroblastoma cells. Our group recently published that NO plays a role in cytotoxicity of low dose BPA in SH-SY5Y neuroblastoma cells [18]. Additionally, it has been shown that NO induces cell death mechanisms in other type of neuroblastoma cell lines [19,20] These observations clarify the fact that doses of BPA at levels 0.05mg/kgbody weight/day, which for a long time was thought by EFSA to be safe, is toxic for the SH-SY5Y neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our results distincly show that different doses (0-100 μM) of BPA administered for different period may change viability and NO levels of SH-SY5Y neuroblastoma cells. Our group recently published that NO plays a role in cytotoxicity of low dose BPA in SH-SY5Y neuroblastoma cells [18]. Additionally, it has been shown that NO induces cell death mechanisms in other type of neuroblastoma cell lines [19,20] These observations clarify the fact that doses of BPA at levels 0.05mg/kgbody weight/day, which for a long time was thought by EFSA to be safe, is toxic for the SH-SY5Y neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 66%
“…Neurotoxic effects of low dose BPA exposure on SH-SY5Y neuroblastoma cells may be explained with increase in the levels of NO as a result from different parameters. Previous report of Ayazgok et al showed that nNOS mRNA level was not changed by low dose BPa treatment in SH-SY5Y neuroblastoma cells [18]…”
Section: Discussionmentioning
confidence: 86%
“…Thus, many institutions and organizations are now looking for ways to reduce the damage caused by BPH-A. In a recent study, it was stated that NO, Caspaze-8 and cytotoxicity increased in the neuroblastoma cell line after low-dose BPH-A exposure (Ayazgok et al, 2018). Guzel et al, conducted that there was an increase in intracellular Ca 2+ ion, apoptosis, and mitochondrial oxidative stress in MCF-7 cells after exposure to BPH-A.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a series of compounds were reported to be capable of inducing tumor necroptosis in different pathways ( Table 1 ) 95 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 . Several of them have been previously known to act by typical antitumor mechanisms, whose new role in necroptosis aid to draw a comprehensive mechanism diagram of these antitumor agents.…”
Section: Necroptosis Inducersmentioning
confidence: 99%
“…Bisphenol A (BPA, 58 ) is an endocrine disruptor with estrogenic and obesogenic activity 42 . SH-SY5Y cells (human neuroblastoma cell line) treated with compound 58 underwent apoptosis within 48 h, then necrosis was occurred and increased gradually 129 . When necroptosis inhibitor 2 was added in combination treatment with compound 58 , necroptosis was replaced by apoptosis, indicating that it induced necroptosis 129 .…”
Section: Necroptosis Inducersmentioning
confidence: 99%